Preparation and Modification of Composite Inorganic Salt Phase Change Materials for Cold Storage - Li Mengxin; Chen Peng; L; Zhongling (Zhileng xuebao)
Aiming at the temperature requirement of 6–7 ℃ in the field of building air conditioning cold storage, a composite inorganic salt phase change material was prepared with Na2SO4?10H2O and Na2HPO4?12H2O as cold storage base materials. The effects of different types and quality additives on the composite inorganic salt system were studied by step cooling curve analysis, differential scanning calorimetry, and the transient plane heat source method. The experimental results show that the final ratio of the modified composite inorganic salt system is 32% Na2SO4?10H2O + 48% Na2HPO4?12H2O + 16% NH4Cl + 1.6% borax + 1.6%CMC + 0.8%nano-TiO2. The phase transformation temperature is 6.1~6.3 ℃. The latent heat of the phase transformation was 130–139 J/g. The undercooling is less than 0.5 ℃, and no phase separation phenomenon exists. The liquid-phase thermal conductivity is 0.798 9 W/(m?K). After 50 cycles, the composite inorganic salt system exhibits good thermal stability.